A Novel Hierarchical Structured Poly(lactic acid)/Titania Fibrous Membrane with Excellent Antibacterial Activity and Air Filtration Performance. (17th February 2016) - Wang, Zhe; Pan, Zhijuan; Wang, Jigen; Zhao, Ruizhi
Abstract : Hybrid poly(lactic acid)/titania (PLA/TiO2 ) fibrous membranes exhibiting excellent air filtration performance and good antibacterial activity were prepared via the electrospinning technique. By varying the composition of the precursor solutions and the relative humidity, the morphologies of PLA/TiO2 fibers, including the nanopores and nanometer-scale protrusions on the surface of the fibers, could be regulated. The distribution of nanopores and TiO2 nanoparticles on the surface of PLA/TiO2 fibers was investigated. Nitrogen adsorption-desorption analysis revealed that nanopores and nanometer-scale protrusions play an important role in improving the specific surface area and nanopore volume of the relevant PLA/TiO2 fibrous membrane. Filtration performance tests conducted by measuring the penetration of sodium chloride aerosol particles with a 260 nm mass median diameter indicated that fibers with a high surface roughness, large specific surface area, and large nanopore volume greatly improved the particle capture efficiency and facilitated the penetration of airflow. Furthermore, the introduction of TiO2 nanoparticles endows the relevant fibrous membrane with antibacterial properties. The as-prepared PLA/TiO2 fibrous membrane loaded with 1.75 wt% TiO2 nanoparticles formed at a relative humidity of 45% exhibited a high filtration efficiency (99.996%) and a relatively low pressure drop (128.7 Pa), as well as a high antibacterial activity of 99.5%.